Effects of ratio of total sulfur amino acid to lysine on finishing-pig growth performance - Lawrence, K.R.; Goesbeck, C.N.; Neill, C.R.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
The objective of this study was to characterize the growth response to total sulfur amino acids (TSAA) and lysine simultaneously to estimate the true-ileal-digestible (TID) TSAA-to-lysine ratio in early finishing pigs. One hundred and twenty-six pigs were used in a 27-d growth study. Pigs (73 to 134 lb) were blocked by sex and weight and were allotted to one of nine dietary treatments with five TID lysine (0.79, 0.87, 0.94, 1.02 and 1.10%) and five TID TSAA (0.53, 0.57, 0.61, 0.66 and 0.70%) concentrations. The highest lysine (1.10%) and TSAA (0.70%) concentrations were combined to form one treatment used in both the lysine and TSAA titrations. In diets evaluating increasing TID lysine, methionine & cysteine ratios were 64 to 66% of lysine; and in diets evaluating increasing TSAA, diets were formulated to 1.10% TID lysine. Increasing TID lysine increased ADG (linear, P<0.01) and improved F/G (quadratic, P<0.10) from d 0 to 14 and from d 0 to 27. No differences (P>0.05) were observed in ADFI. Increasing TSAA had no effect (P<0.05) on ADG or F/G, but pigs fed the diet containing 0.70% TSAA had numerically greater ADG than did pigs fed lower rates. As TSAA concentration increased to 0.61%, feed efficiency numerically improved (P = 0.16). Using a TID lysine requirement of 1.02% and TID TSAA requirement of 0.61% suggests a TSAA-to-lysine ratio of 60%. The surface response analysis suggests a similar TSAA-tolysine ratio of 59% for overall F/G.
Keywords: Swine; TSAA; Lysine; Pigs; Finishing pigs